Uji Daya Hasil Lanjutan Galur-Galur Padi (Oryza sativa L) Sawah Irigasi Berpotensi Hasil Tinggi - Aulia, Gebby Reza; Afifah, Lutfi; Surjana, Tatang; Pramudyawardani, Estria Furry; Dewi, Ratna Sari; Roza, Celvia (Indonesian Journal of Agrotech, 2023)
The continual of the same high yield variety (HYV) is not recommended because it can cause resistance breakage against pest disease. One of the Indonesian Center for Rice Research (ICRR) main tasks is to establish new rice varieties with high yield potential and other better characteristics than the previous HYVs. Yield Test of promising lines aimed to select the yield potential, resistance to major pests, and rice quality to be further tested in a breeding processes. The research was carried out in the ICRR Experimental station, located in Sukamandijaya Village, Subang Regency, West Java. This study used a randomized complete block design with 4 replications consisting of 14 advanced generation lines, namely G1 (BP 30533D-SKI-4-3-1), G2 (BP 19210e-6-2-1- 3), G3 (BP 30531D-SKI-24-3), G4 (BP 30531D-SKI-1-2-3), G5 (BP 30534D-SKI-6-1), G6 (BP 30533D-SKI-4- 3-2), G7 (BP 30485E-SKI-9-5-2-0), G8 (BP 30533D-SKI-29-1-1-Ski), G9 (BP 31507D-SKI-1-1-1) , G10 (BP 30475c-SKI-6-4-1-5), G11 (Koshi CSSL [IR64] SL2129), G12 (BP 30533D-SKI-29-1-1-Skb), G13 (BP 31456D-SKI- 7-1), G14 (BP 31523D-SKI-2-1-0-0), and 2 checks (A (INPARI 33) and B (INPARI 32)). The results of the analysis of variance and the post hoc test used was DMRT test The data were analyzed by analysis of variance on yield did not show a significant difference between the lines tested and the best checks INPARI 33 ( 6.18 t/ha MPD). The G1 and G11 lines showed a moderately resistant response to bacterial leaf blight (HDB) IV, both lines were recommended for further testing